Offshore Pipelines - Guo, PhD Boyun
More than a third of the worldwide growth in drilling is expected to come from offshore, making the development of offshore pipelines an extremely hot topic in the energy industry. Offshore Pipelines is the most up-to-date reference for engineers and developers challenged with bringing oil and gas onshore. Written primarily for engineers and management personnel working on offshore and deepwater oil and gas pipelines, this book brings together the authors' years of experience on a variety of pipeline projects. It offers cost-effective approaches for developing pipeline systems. By presenting p.